Digital Payment (QRIS) System Training and Mentoring for MSMEs in Prayungan Village, East Java - May Shinta Retnowati; Ageng Riz’y Waluyo; Muhammad Abdul Aziz (LPPM Universitas Ma Chung, 2022)
Post pandemic of COVID-19 has opened some opportunities and challenges for everyone to be able to optimize digital activities. The digitalization concept that has been implemented by entrepreneurs who can stand despite the global pandemic outbreak can be an option even with the very potential for entrepreneurs to maximize profits. The practice of using QRIS in Indonesia is still only felt for large markets in urban areas, so it has not been maximally penetrated by markets in rural areas and border areas. As is the case with micro, small and medium enterprises (MSMEs) with home-based models that exist in rural areas and only have small capital. As for MSME actors in Prayungan Village, Sawoo District, Ponorogo Regency, the QRIS payment system has the potential to be implemented. This service activity is carried out by Darussalam Gontor University using training and mentoring methods regarding the benefits of the QRIS digital payment system for MSMEs. The purpose of this service is to provide education to MSME actors and be able to transform in the digital era. The results of this service were the realization of making QRIS for MSMEs and the survey results reached 80% who were very satisfied with the implementation of training and assistance for the QRIS payment system for MSMEs.